Driver machine-tool adaptations and its technological capabilities - Erokhin V.V. (Научно-технический вестник Брянского государственного университета)
The article presents the design of the driver machine-tool adaptations based on rigid and floating center for machine tools of the turning group, as well as their technological capabilities in providing quality workpieces. The main characteristic of the effective performance of the flanged clamping device adopted its capacity and ensure dimensional accuracy of workpieces surfaces. Clamping ability Pedestrian equipment is determined by the setting of the maximum torque that can be transferred to the workpiece. The basic advantages and disadvantages of various design solutions flanged machine tool accessories. The data processing accuracy and productivity, rigidity devices with different types of driver machine-tool adaptations.